(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Childhood illnesses in early age, including acute respiratory infections, gastroenteritis, and immune system disorders, pose a serious threat to children’s health and hinder the development of millions of children worldwide. Community nurses play a vital role in preventing these illnesses, as they conduct constant monitoring, education, and interventions within the family environment. This article thoroughly assesses the effectiveness of prevention programs led by community nurses based on a systematic review of scientific studies conducted from 2023 to 2025. The reviewed studies show that nurse interventions reduce the incidence of illnesses by 15-25%, increase vaccination coverage by 20-30%, and improve early childhood development indicators, such as cognitive and motor skills, by 10-15%. Additionally, nurses educate mothers and family members on early detection of disease risks and maintaining nutrition hygiene skills, which can potentially reduce infant mortality rates by 8-12%. However, studies highlight the lack of resources and insufficient number of nurses in rural areas, limiting program effectiveness by 40%. The article provides detailed recommendations for preventing childhood illnesses in the post-pandemic period, including the implementation of remote monitoring systems, strengthening family support programs, and standardizing nurse training in developing countries. These approaches aim to enhance children’s health and mitigate socio-economic inequalities, as early illnesses often manifest more severely in low-income families. Research findings indicate that community nurse-led programs not only reduce physical symptoms but also support children’s mental and emotional development, as chronic illnesses can impact stress and family relationships. Furthermore, the article discusses the economic benefits of prevention in a global context, as effective programs can reduce disease treatment costs by 20-35% annually. Consequently, this article provides practical guidance for health professionals, policymakers, and families, emphasizing the need to strengthen the role of community nurses in preventing illnesses in early childhood.